THE ROLE OF INSURANCE IN REGULATING FOREIGN ECONOMIC ACTIVITY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Foreign economic activity is great importance to countries and businesses in the modern world. However, the specific characteristics of foreign economic activity, in particular, the instability of the world market, exchange rate fluctuations, political risks, natural disasters and other various risks, make foreign economic activity one of the specific risky processes. Therefore, risk management is important in the effective implementation of foreign economic activity. One of the most effective means of risk management is insurance.